2012
DOI: 10.1097/tp.0b013e3182590d2e
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Effect in Desensitization With Intravenous Immunoglobulin and Rituximab in Highly Sensitized Patients

Abstract: These results suggested that pretransplant desensitization with IVIG and rituximab was not successful in highly sensitized kidney transplant candidates with cPRA levels higher than 90%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 19 publications
3
65
0
Order By: Relevance
“…In the second study, 7 titled "infusion of high-dose intravenous immunoglobulin fails to lower the strength of human leukocyte antigen antibodies in highly sensitized patients," the authors confirmed that HLA antibody profiles, measured by calculated PRA, showed no significant change in response to IVIg treatment. The third study 8 also documented that IVIg-even with rituximab-did not lead to any significant reduction in patients' anti-HLA-Ia Abs calculated by PRA levels or MFI measured with Luminex single antigen beads. Importantly, none of these studies corroborate previous claims of the reduction of HLA antibodies (calculated panel reactive antibody) in sensitized patients undergoing desensitization with high-dose IVIg.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the second study, 7 titled "infusion of high-dose intravenous immunoglobulin fails to lower the strength of human leukocyte antigen antibodies in highly sensitized patients," the authors confirmed that HLA antibody profiles, measured by calculated PRA, showed no significant change in response to IVIg treatment. The third study 8 also documented that IVIg-even with rituximab-did not lead to any significant reduction in patients' anti-HLA-Ia Abs calculated by PRA levels or MFI measured with Luminex single antigen beads. Importantly, none of these studies corroborate previous claims of the reduction of HLA antibodies (calculated panel reactive antibody) in sensitized patients undergoing desensitization with high-dose IVIg.…”
Section: Discussionmentioning
confidence: 99%
“…Three recent clinical studies document that IVIg preparations were unable to reduce HLA Abs. [6][7][8] In the first, 6 IVIg failed to lower the mean percentage of pretransplant HLA Abs observed before IVIg infusion (85% before, 80% after IVIg; P 5 .1). On the contrary, an increase in anti-HLA-Ia Abs was observed after IVIg in 27% of the patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The methods for microarray analysis are described in detail in our previous publications (20,21). Gene Set libraries were taken from the Molecular Signatures Database (22), and new libraries were generated by mapping HUGO gene identifiers to the University of Alberta, Edmonton, pathogenesis-based transcripts (PBT; http:// transplants.med.ualberta.ca/Nephlab/data/gene_lists.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Recently Marfu et al examined the use of IVIG (2g/kg) and rituximab (1 dose 375mg/m2) for immunomodulation of patients on the deceased donor waiting list [80]. They found that in patients with cPRA >50%, treatment with IVIG and rituximab did not increase rates of transplantation.…”
Section: Modulation Of the Immune Response In Recipients With Crossmamentioning
confidence: 99%